2014
DOI: 10.1002/acp.3103
|View full text |Cite
|
Sign up to set email alerts
|

Question Types, Responsiveness and Self‐contradictions when Prosecutors and Defense Attorneys Question Alleged Victims of Child Sexual Abuse

Abstract: We examined 120 trial transcripts of 6-to 12-year-old children testifying to sexual abuse. Age and attorney role were analyzed in relation to question types, children's responsiveness and self-contradiction frequency. A total of 48,716 questionresponse pairs were identified. Attorneys used more closed-ended than open-ended prompts. Prosecutors used more invitations (3% vs. 0%), directives, and option-posing prompts than defense attorneys, who used more suggestive prompts than prosecutors. Children were more un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
96
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(109 citation statements)
references
References 45 publications
12
96
1
Order By: Relevance
“…Instead, over 80% of prosecutors’ what/how questions were static. These findings are consistent with research on prosecutors’ questions about abuse itself, with very small percentages of invitations (Andrews et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Instead, over 80% of prosecutors’ what/how questions were static. These findings are consistent with research on prosecutors’ questions about abuse itself, with very small percentages of invitations (Andrews et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…First, invitations and cued invitations are uncommon in forensic interviews unless interviewers have been specially trained (Sternberg et al, ). Indeed, prosecutors at trial ask very few invitations when they question children about the details of sexual abuse (Andrews, Lamb, & Lyon, ). Prosecutors might use a few “What happened?” or “What happened next?” questions, which would qualify as invitations or as cued invitations, but it is unlikely that a prosecutor would use a cued invitation simply to elicit additional information (using the form “Tell me more about…”) for two reasons.…”
Section: Interview Instructionsmentioning
confidence: 99%
“…Unfortunately, the Court did not report how the child was asked about clothing. Research examining how children are questioned about sexual abuse in court has shown that yes/no questions predominate (Andrews, Lamb, & Lyon, ; Hanna, Davies, Crothers, & Henderson, ; Klemfuss, Quas, & Lyon, ; Stolzenberg & Lyon, ). Hence, it is likely that the child in Emmett was asked yes/no questions about his and the defendant's clothing placement (e.g., ‘Were your/his clothes on?’ or ‘Were your/his clothes off’?…”
Section: Introductionmentioning
confidence: 99%
“…Most often, children are questioned with yes/no or forced-choice questions containing spatial terms (e.g., “Were your clothes on or off?”) (Stolzenberg & Lyon, in press). Although developmental psychologists have mapped out children’s emerging understanding of spatial language, focusing on prepositions and verb phrases (e.g., Farran & Atkinson, 2016), and a great deal of applied psychology research has examined the effects of question type on children’s eyewitness performance (e.g., Andrews, Lamb, & Lyon, 2015), little is known about how well young children answer different types of questions incorporating spatial language. In practice, this is particularly important when there is a less than perfect fit between the situation and the spatial term.…”
mentioning
confidence: 99%